2023
DOI: 10.1097/md.0000000000032882
|View full text |Cite
|
Sign up to set email alerts
|

The role of claudin 18.2 and HER-2 in pancreatic cancer outcomes

Abstract: To examine the prognostic value of claudin 18.2 (CLDN18.2) and human epidermal growth factor receptor-2 (HER-2) expression in patients with resected pancreatic ductal adenocarcinoma (PDAC). This study enrolled patients who underwent surgery and were diagnosed with PDAC at Suleyman Demirel University Hospital, Turkey between 2015 and 2019. Sixty-eight patients with resected PDAC treated at a medical oncology clinic were assessed. All patients were over the age of 18 years, underwent follow-up and treatment in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Previous studies, which investigated the expression of Claudin 18.2 in PDAC showed higher expression rates [ 14 , 21 , 22 ]. However, other studies showed expression rates, that align with our study [ 9 , 20 ]. These differences could be explained by the use of various antibodies and cut-off values for CLDN18.2 positivity.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Previous studies, which investigated the expression of Claudin 18.2 in PDAC showed higher expression rates [ 14 , 21 , 22 ]. However, other studies showed expression rates, that align with our study [ 9 , 20 ]. These differences could be explained by the use of various antibodies and cut-off values for CLDN18.2 positivity.…”
Section: Discussionsupporting
confidence: 92%
“…We also found that Claudin 18.2 was an independent factor for favorable prognosis in patients with PDAC (HR = 0.686, 95 % CI = 0.492–0.956, p = 0.026). Supporting our findings, Kayikcioglu et al report a significant correlation between patients with high Claudin 18.2 expression and better overall survival in a patient cohort of sixty-eight patients [ 20 ]. On the contrary, high Claudin 18.2 expression was correlated with lymph node and distant metastases as well as poor patient survival [ 22 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations